(untitled) (Research, Society and Development, 2020)
Organic substrates can improve the organic matter content of the soil, the availability of nutrients and, consequently, there are quality seedlings. The objective was to evaluate the development of Capsicum chinense Jacq seedlings produced in an alternative organic substrate. A randomized block design was used, with six treatments and four repetitions. The treatments were the combinations of bee nests (NA) and commercial substrate Click® (SC), combinations of substrates formulated with the following proportions based on their volume (S1=NA100%SC0%, S2=NA80%SC20%, S3=NA60%SC40%, S4=NA40%SC60%, S5=NA20%SC80% and S6=nA0%SC100%). Commercial seeds of biquinho pepper were used. Two substrates were tested [consisting of an alternative substrate (NA = bee nest) and a commercial substrate (SC = Click Mudas®)]. Commercial seeds of Biquinho-type pepper were used. At 56 days after sowing, plant height, stem diameter, number of leaves, root length, dry mass of roots (MSR) and shoots (MSA), total dry mass, MSA/MSR ratio, robustness quotient and Dickson quality index were measured evaluated at 56 days after seedlings. The highest seedling qualities were observed in the substrates (S1=NA100%SC0%, S2=NA80%SC20%, S3=NA60%SC40% and S4=NA40%SC60%), resulted in a higher quality of Biquinho-type pepper seedling; however, it is recommended to use S1 for reducing production costs and being a material accessible to growers.